Kształt pamięci. Tatrzańskie doświadczenie przyrody w pomniku Władysława Hasiora „Prometeusz rozstrzelany” - Rolando, Bianka (Humaniora. Czasopismo Internetowe, 2024)
The aim of this article is to present the context of using materials naturally occurring in mountain nature: stone, water, wind, in the implementation of the monument by Władysław Hasior “Prometheus Executed” (1964). The monument commemorates twenty hostages shot in a clearing on the road to Kuźnice in 1944, today’s Aleja Przewodników Tatrzańskich in Zakopane. Hasior’s sculptural symbolism is based on a dialogue with nature, which loses its innocence, becoming the place where the crime took place. The article will describe the sculptor’s methodology of work towards the interpretation of nature, and its role in outlining the shape of the memory of the war crime and confronting it with the Tatra nature.